Application of a new multi-metric index with a comparative analysis for assessing the environmental status of Posidonia oceanica meadows (Algeria, Southern Mediterranean) - SENGOUGA, AMINA; BOUMAZA, SALIMA; MISRAOUI, ALI; ZERROUKI, MOHAMED; BOUDJADJA, RIHEM; LOUANCHI, FERIAL; SEMROUD, RACHID (Mediterranean Marine Science, 2025)
Several biotic indices have been developed over the last two decades to assess water and habitat quality in the Mediterranean Sea, with Posidonia oceanica serving as a Biological Quality Element (BQE). To contribute to this effort, we created a new Multi- metric Index for the Algerian coast based on P. oceanica (MIAPo), adapted from existing indices and calibrated at eight sites with varying human pressures. This study also intends to compare the performance of MIAPo and PREI (P. oceanica Rapid Easy Index) in assessing the ecological status of coastal Algerian waters. MIAPo was built using multivariate analyses that combined five metrics: lower limit depth, leaf area index, epiphytic load, leaf tannin cell density, and leaf nitrogen content. To accurately interpret MIAPo and PREI, a Pressure Index (PI) was calculated, taking into account urbanization, agriculture, coastal population, uncontrolled dumping, fishing activity, rivers, industrial activity, and urban effluents. According to the Water Framework Directive (WFD) classification, the indices MIAPo and PREI demonstrated high comparability in the ecological status assigned to the studied sites (62.5% agreement), which was validated using Spearman’s correlation coefficient (R = 0.88; p = 0.004). In addition, MIAPo and PREI show a strong correlation with the PI (R = -0.96; p = 0.0002 and R = -0.80; p = 0.02, respectively). The proposed index, MIAPo, provides a more comprehensive measure than PREI for the assessment and monitoring of Algerian coastal waters. Nonetheless, more field data collection is needed to expand the use of this valuable tool on a broader geographical scale.